Big Data in Healthcare Transformation: A Short Review - Ghaleb, E.A.A. (Institute of Electrical and Electronics Engineers Inc., 2022)
With the rising expense of healthcare and rising health insurance premiums, preventive healthcare and wellness are necessary. Additionally, a new era in medical records in the healthcare industry, digitalization has ushered in a paradigm shift. As a result, the healthcare industry is seeing an increase in data volume., complexity, variety, and timeliness. As healthcare professionals explore ways to reduce costs while enhancing care processes, delivery, and management, big data (BD), appears as a viable option with the potential to alter the sector. This paradigm changes from reactive to proactive healthcare has the potential to result in total cost savings and eventually economic development. However, while the healthcare business leverages the potential of BD, privacy concerns remain a top priority as new threats and vulnerabilities emerge. We describe the state-of-the-art privacy challenges in BD related to the healthcare business in this study. Â© 2022 IEEE.